Investigation of light delivery geometries for photoacoustic applications using Monte Carlo simulations with multiple wavelengths, tissue types, and species characteristics - Sowers, Timothy (J Biomed Opt, 2020)
Combined ultrasound and photoacoustic imaging systems are being developed for biomedical and clinical applications. One common probe configuration is to use a linear transducer array with external light delivery to produce coregistered ultrasound and photoacoustic images. The diagnostic capability of these systems is dependent on the effectiveness of light delivery to the imaging target. We use Monte Carlo modeling to investigate the optimal design geometry of an integrated probe. Simulations are conducted with multiple tissue compositions and wavelengths. The effect of a skin layer with the thickness of a mouse or a human is also considered. The model was validated using a tissue-mimicking gelatin phantom and corresponding Monte Carlo simulations. The optimal illumination angle is shallower with human skin thickness, whereas intermediate angles are ideal with mouse skin thickness. The effect of skin thickness explains differences in the results of prior work. The simulations also indicate that even with identical hardware and imaging parameters, light delivery will be up to [Formula: see text] smaller in humans than in mice, due to the increased scattering from thicker skin. Our findings have clear implications for the many researchers using mice to test and develop imaging methods for clinical translation.